Risk modeling, assessment, and management - Haimes, Yacov Y., 1936-2022 (Wiley series in systems engineering and management, 2016)
"This book examines risk analysis, focusing on quantifying risk and constructing probability in conjunction with real-world decision-making problems, including institutional, organizational,and political considerations"--Resumé vydavatele